DAMPAK PENANAMAN SERAI WANGI TERHADAP LINGKUNGAN DIHUBUNGKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (STUDI KASUS DI KECAMATAN SUKANAGARA) - Sarah Pasha Fadilla; Hesti Dwi Astuti (Universitas Suryakancana, 2019)
Environmental problems are increasingly prominent and complex issues in line with the increasingly intensive human intervention on the environment. Aware that human activities in the context of meeting their needs can have an impact on their environment, humans strive to carry out environmental management. Planting lemongrass in the district of Sukanagara turned out to harm the environment such as drought, landslides and floods, nutrient-poor. The results showed that some people considered that the planting of lemongrass was not so damaging to the environment. Hence, it lacked a sense of care for the surrounding environment resulting in environmental damage. The efforts that can be carried out are as follows: Planting system, with horticulture planting patterns, Planted in the form of terracing or swales, by intercropping, evaluating soil fertility.Keywords: Citronella Planting; Environmental protection; management.